Choroidal Structural Changes in Tubercular Multifocal Serpiginoid Choroiditis. (18th August 2018) - Agarwal, Aniruddha; Agrawal, Rupesh; Khandelwal, Neha; Invernizzi, Alessandro; Aggarwal, Kanika; Sharma, Aman; Singh, Ramandeep; Bansal, Reema; Sharma, Kusum; Singh, Nirbhai; Gupta, Vishali
ABSTRACT: Purpose : To assess choroidal vascular changes among patients with tubercular multifocal serpiginoid choroiditis (TB MSC) using previously validated techniques. Methods : Patients with TB MSC (n = 18) and healthy controls (n = 30) underwent enhanced-depth imaging optical coherence tomography (EDI-OCT) imaging. Using previously validated algorithm of image binarization, EDI-OCT scans were segmented to derive total choroidal area, luminal area, stromal area, and choroidal vascularity index (CVI). Results : There was a statistically significant difference in the CVI between controls (66.90 ± 1.77%) and TB MSC patients (65.46 ± 2.53%; p < 0.001). There was significant reduction in CVI at follow-up (3 months) (63.77 ± 3.91%; p = 0.05). The choroidal thickness was higher in TB MSC compared to controls (278.90 ± 57.84 µm versus 329.33 ± 27.69 µm; p = 0.001). Conclusions : CVI provides insight into structural changes in choroid in TB MSC. During the active disease, there is relative decrease in choroidal vascularity. As the lesions heal, choriocapillaris atrophy occurs with remodeling of choroid.